Akibat Hukum Putusan Pernyataan Pailit Debitor terhadap Kreditor (Analisis Putusan Mahkamah Agung Nomor 443K/Pdt.Sus/2012) - Fedriyanti, Irma; Sutiarnoto, Sutiarnoto; Perdana, Surya (Mahesa Research Center, 2021)
The purpose of this paper is to review and analyze legal provisions in the case of a decision on a debtor's bankruptcy statement against creditors, to review and analyze legal remedies that can be taken by creditors in the event that the debtor's asset value has not been able to pay off debts to creditors and To review and analyze the legal consequences of bankruptcy statements by debtors in the Decision of the Commercial Court of the Central Jakarta District Court Number 12 / PAILIT / 2012 in conjunction with the Decision of the Supreme Court No.443K / Pdt. Sus / 2012. This type of research is normative legal research. Data analysis is the process of organizing and sorting data into categories and basic description units, so that themes are found and work hypotheses can be formulated, as suggested by the data. The data analysis was done qualitatively. With associated research objectives. The results showed that the legal provisions in the stipulation of a decision on a debtor bankruptcy statement against creditors are regulated in Law Number 37 of 2004, namely in article 2 paragraph (1), which explains that the requirements for filing a bankruptcy application are two or more creditors and have not paid off the minimum debt. against one creditor and the debt is due. Legal remedies that can be taken by creditors in the event that the value of the debtor's assets has not been able to pay off the debt to the creditor is to bankrupt the new business of the debtor if the debtor is still in default and does not pay off the debt even though it has been collected properly before.